TOFU PRODUCTION OPTIMIZATION USING INTEGER LINEAR PROGRAMMING THROUGH BRANCH AND BOUND APPROACH - Ani Putri, Khairunnisa (Pena Cendekia Insani, 2024)
This research optimizes tofu production at Sumedang Mas Ponimin Tofu Factory, Medan, which produces white tofu, yellow tofu, and pong tofu. Facing the challenges of production efficiency and profit improvement due to manual methods, an optimization model was developed using simplex and branch and bound methods. Primary and secondary data were used to evaluate raw material availability, production capacity, and profitability. The results showed an increase in daily production from 118 to 142 boards and an increase in profit from Rp1,888,500 to Rp2,263,500. This research confirms the effectiveness of applying mathematical optimization methods in improving operational efficiency and decision-making in the food industry.